Taking Access to the Community: An Ecological Systems Framework for In‐Home Counseling With Older Adults. Issue 1 (8th April 2020) - Bettis, Janelle; Kakkar, Shannon; Chan, Christian D.
Abstract : Bronfenbrenner's (1977) ecological systems theory is a holistic framework placing an individual in a system's context to address their concerns. This article offers a case study demonstrating use of the theory with older adults and the in‐home setting. Implications for the counseling field and future research needs are discussed.